2019
DOI: 10.1097/md.0000000000015810
|View full text |Cite
|
Sign up to set email alerts
|

Systematic estimation of BMI

Abstract: The prevalence of overweight–obesity has increased sharply among undergraduates worldwide. In 2016, approximately 52% of adults were overweight–obese. This cross-sectional study aimed to investigate the prevalence of overweight–obesity and explore in depth the connection between eating habits and overweight–obesity among Chinese undergraduates. The study population included 536 undergraduates recruited in Shijiazhuang, China, in 2017. They were administered questionnaires for assessing demographic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 33 publications
0
10
0
2
Order By: Relevance
“…Shan provided a preliminary description, and we conducted a further analysis of that research. 10 We revealed several main findings. First, we found that participants’ sex and region of residence affected BMI.…”
Section: Discussionmentioning
confidence: 86%
“…Shan provided a preliminary description, and we conducted a further analysis of that research. 10 We revealed several main findings. First, we found that participants’ sex and region of residence affected BMI.…”
Section: Discussionmentioning
confidence: 86%
“…BMI was estimated by asking the patients to report their body weight (kg) and height (m). A BMI of <18.5 kg/m 2 was considered underweight and >24.9 kg/m 2 was deemed overweight or obese [26].…”
Section: Measurements and Variablesmentioning
confidence: 99%
“…LDLRan aldaera asko aurkitu direnez, haien eragina aurresateko gai den software baten sorrera posible eta oso lagungarria izango litzateke. Badaude edozein genetan gertatutako mutazioen eragina aurresaten duten software batzuk (PolyPhen-2 eta SIFT) baita LDLRarekiko espezifikoak direnak ere (SFIP-MutID) (Adzhubei et al, 2010), (Sim et al, 2012), (Guo et al, 2019). Hala ere, kontraesanak daude haien aurreikuspenen artean, eta aldaera onberen kasuan zehazki ez daukate oso asmakuntza-tasa altua.…”
Section: Sarrera Eta Motibazioaunclassified
“…Dieta mediterraneoa patroi dietetiko orekatu eta osasungarriaren adibide bat da (Galbete et al, 2018), eta dieta osasuntsu bati egotz dakiokeen kalitate-maila ematen digu. Hala ere, aurretik egindako azterlanek erakutsi dute dietak kalitate txarra duela unibertsitateko biztanleen artean , eta nabarmentzekoa da loditasuna garatzeko arrisku handiagoa dakarten azukre, koipe eta sodio asko kontsumitzen direla (Shan et al, 2019). Horregatik guztiagatik, unibertsitateko ikasleak biztanleria zaurgarria dira, eta elikadura-ohitura txarrak izateko arrisku handia dute.…”
Section: Arloko Egoera Eta Ikerketaren Helburuakunclassified